First record of Paraprionospio coora Wilson, 1990 (Polychaeta: Spionidae) from the Mediterranean Sea) - YOKOYAMA, H.; DAGLI, E.; CINAR, M.E. (Mediterranean Marine Science, 2010)
The spionid polychaete Paraprionospio pinnata (Ehlers, 1901) has been widely reported from the Mediterranean Sea. We examined some specimens belonging to the genera Paraprionospio that had been collected from the Aegean Sea, Sea of Marmara and the Spanish Mediterranean coast, and identified them as Paraprionospio coora Wilson, 1990, which is new to the Mediterranean fauna. This finding indicates that P. coora has a widespread geographical distribution in Australia, Far East and the Mediterranean, and suggests that the previous records of P. pinnata from the Mediterranean are questionable.